Chronic stress, sense of coherence and risk of type 2 diabetes mellitus. Issue 1 (January 2019) - Madhu, S.V.; Siddiqui, Azaz; Desai, N.G.; Sharma, S.B.; Bansal, A.K.
Abstract: Aims: The study was conducted to ascertain whether chronic stress and sense of coherence are associated with risk of type 2 diabetes mellitus. Methods: Stress questionnaires - Presumptive Stressful Life Events Scale (PSLES), Perceived Stress Scale (PSS) and Sense of Coherence (SOC) - were administered to 500 Newly Detected Diabetes Mellitus (NDDM) cases and 500 Normal Glucose Tolerance (NGT) controls recruited following 75 g OGTT. Assessment of stress was completed before the diagnosis of diabetes was revealed to them. Results: PSLES and PSS scores were significantly higher and SOC score was significantly lower in NDDM subjects compared to those with NGT. PSLES and PSS correlated positively with anthropometric parameters (waist circumference, BMI), glycemic parameters (FPG, 2 hPG, A1C) and HOMA-IR and inversely with HOMA-β whereas SOC correlated inversely with glycemic parameters (FPG, 2 hPG, A1C) and HOMA-IR and positively with HOMA-β. In stepwise logistic regression analysis, SOC emerged as the strongest independent predictor of diabetes (OR: 0.774) after HOMA-IR (OR: 1.621) and BMI (OR: 1.288). Other significant predictors included PSS (OR:1.153), PSLES-LT (OR: 1.005) and HOMA-β (OR: 0.894). Conclusion: Chronic stress and low sense of coherence are associated with a higher risk of type 2 diabetes mellitus.